The Urgency of Developing E-Law Consult Application for Legal Protection of Female Migrant Workers in Central Java - Megafury Apriandhini; Dian Ratu Ayu Uswatun Khasanah; Ronald Jolly Pongantung (Faculty of Law, Universitas Pekalongan, 2025)
Indonesian migrant workers often receive less than proper treatment and some of them are caught in several cases so that they are threatened with severe punishment and some are even sentenced to death. The essence of providing legal protection for Indonesian female migrant workers is protection against security guarantees from all forms of violence, both physical and psychological, or in other words to provide protection against arbitrary actions by an individual or group. The purpose of this study is to determine the urgency of the e-law consult application for legal protection of female migrant workers in Central Java. The e-law application is expected to help female migrant workers to communicate more easily with the migrant service. The results obtained from this study are based on the questionnaire that has been distributed to respondents, namely an average percentage of 90%, meaning that respondents strongly agree if the e-law consult application is made and designed according to respondent input. The idea of ​​developing an e-law consult application is classified as very good to make it easier for migrant workers to get information and communicate with the Manpower Office, Ministry of Manpower, BP2MI.